North Korea Threat: How Should ASEAN Respond? - Han, David Guo Xiong (2017)
Although ASEAN should be concerned about the North Korean threat given the grave security implications to the wider Asia-Pacific region, ASEAN should be mindful of its actual raison d’etre to avoid distorting its credentials and relevance in relation to the Korean Peninsula crisis.